Ligas Acadêmicas: motivações e críticas a propósito de um repensar necessário - Hamamoto Filho, Pedro Tadao [UNESP] (Associação Brasileira de Educação Médica, 2011)
Student Leagues have gained increasing presence in the everyday lives of student doctors. The reasons why students seek them arise from their needs for clinical experience, socialization and professional qualification. However, several Leagues have shifted away from the principles of higher education extension studies, giving rise to a parallel curriculum, filling curricular gaps, providing premature specialization and reinforcing bad learning habits. It is therefore necessary to reconsider Student Leagues in terms of their social and academic relevance, their objectives and responsibility in relation to medical training, interdisciplinarity, the SUS and ethical principles, with a view to integration between education, research and university extension programs, in order to meet public demands and contribute toward medical training.

Ligas Acadêmicas têm ocupado o cotidiano do estudante de Medicina de forma crescente. As motivações pelas quais os estudantes as procuram estão atreladas à necessidade de vivência clínica, de socialização e de qualificação profissional. Muitas Ligas, porém, têm se distanciado do propósito da extensão universitária, abrindo espaço para o currículo paralelo, o preenchimento de lacunas curriculares, a especialização precoce e o reforço de vícios acadêmicos. Diante disso, é necessário repensar as Ligas Acadêmicas no âmbito de sua relevância social e acadêmica, de seus objetivos e de sua pactuação com a formação médica, com a interdisciplinaridade, com o SUS e com princípios éticos, visando à integração entre ensino, pesquisa e extensão universitária, para sanar demandas populacionais e contribuir com a formação médica.
Student Leagues: motivations and criticisms regarding a necessary reconsideration
Keywords: Education, Medical; Curriculum; Univeristy Extension; Student Leagues; Students, Medical; Community Institutional Relations; Educação Médica; Currículo; Extensão Universitária; Ligas Acadêmicas; Estudantes de Medicina; Relações Comunidade; Instituição